Stem gall nematode on Desmodium ovalifolium in Colombia - Lenné, Jillian M. (Scientific Societies, 1983)
A stem gall nematode is reported for the first time on the promising tropical pasture legume Desmodium ovalifolium CIAT 350 in Colombia. Stem galling was usually associated with damage caused by animal trampling. The nematode has been identified as a new genus of the family Anguinidae.